Subchronic Toxicity Study of Alternanthera philoxeroides in Swiss Albino Mice Having Antioxidant and Anticoagulant Activities - Shahad Saif Khandker; Morshed Alam; Forhad Uddin; Ummay Mahfuza Shapla; Nafisa Lubna; Tanusree Amy Mazumder; Mahfuza Marzan; Milon Mondal; Md Ibrahim Khalil; Nurul Karim; Md Salman Shakil; Md Sakib Hossen (Journal of Toxicology)
Alternanthera philoxeroides, a tropical herb and edible vegetable, has been popular as a medicinal plant. Applying in vitro approach, we initially attempted to assess the phytochemicals, bioactive chemicals, as well as antioxidant and anticoagulant activities of this plant. Following that, the in vivo toxicological effects of methanolic extracts of A. philoxeroides using different doses on the kidney, heart, lung, liver, stomach, brain, and blood of female Swiss Albino mice were investigated. We estimated phytochemicals content as well as antioxidant activity through DPPH, NO, CUPRAC, and reducing power assays, followed by the anticoagulant activities of PT  and aPTT  and bioactive compounds using HPLC. To confirm the biocompatibility of A. philoxeroides extracts, histopathological and hematological parameters were examined in a mice model. Total phenol, flavonoid, and tannin content in A. philoxeroides was 181.75 ± 2.47 mg/g, 101.5 ± 3 .53 mg/g, and 68.58 ± 0.80 mg/g, respectively. Furthermore, the HPLC study confirmed the presence of four phenolic compounds: catechin, tannic acid, gallic acid, and vanillic acid. The methanolic extract of A. philoxeroides showed considerable antioxidant activity in all four antioxidant assay methods when compared to the standard. In comparison to ascorbic acid, A. philoxeroides also demonstrated a minor concentration-dependent ferric and cupric reduction activity. In vivo evaluation indicated that A. philoxeroides extracts (doses: 250, 500, and 1000 mg/kg) had no negative effects on the relative organ or body weight, or hematological indicators. Our study concluded that A. philoxeroides had significant antioxidant and anticoagulant activities and demonstrated no negative effects on the body or relative organ weight, histopathological, and hematological indices in the mouse model.